THE ANALYSIS OF THE INFLUENCE OF FINANCIAL PERFORMANCE, COMPANY SIZE, OWNERSHIP STRUCTURE, LEVERAGE AND COMPANY GROWTH ON COMPANY VALUES IN FOOD AND BEVERAGE INDUSTRY COMPANIES LISTED IN IDX 2012-2016 PERIOD - Mahzura, Tengku Alvi Syahri (Asosiasi Dosen Akuntansi Indonesia, 2018)
This study aims to determine and analyze the factors that influence the value of the company in the food and beverage industry sector companies listed on the Indonesia Stock Exchange. The factors tested in this study are financial performance through profitability ratios namely return on equity (ROE), company size, institutional ownership, managerial ownership, leverage (debt to equity ratio) and company growth. This research is causal associative research using secondary data. The population of this study is as many as 14 companies which are food and beverage companies listed on the Indonesia Stock Exchange in 2012-2016. The sampling technique used was side purposive with the number of 70 observations (14 companies x 5 years). The data was processed using the multiple linear regression statistical test method using SPSS software (Statistical Package for the Social Science). The results of this study prove that the variables of return on equity (ROE), company size, institutional ownership, managerial ownership, leverage (debt to equity ratio) and company growth simultaneously affect the value of the company. Partially return on equity (ROE) and leverage (debt to equity ratio) that affect the value of the company, while the rest, namely the variable size of the company, institutional ownership, managerial ownership and company growth does not affect the value of the company.